Computer aided dynamic simulation of polycentric above-knee prosthesis - Li, Teng. (2008)
Effective restoration of walking and standing of handicapped humans is an important element which improves their quality of life. To meet such a need, the mechanical substitute or prosthesis must provide support and stability as well as behave like a normal limb for various activities. This thesis presents the study of the effectiveness of an above-knee prosthesis with a four-bar linkage polycentric knee joint and a magnetorheological damper controller. A kinematic model of human locomotion is described. Using the model, a series of studies on kinematics, inverse dynamics and dynamic analysis are conducted to simulate the gait of an amputee-prosthesis system. Kinematic analysis shows that the motion of the prosthetic shank can be made very close to that of normal walking motion. The stability of the four-bar linkage polycentric knee prosthesis is then analyzed in stance phase. It is shown that such a device has an elevated instantaneous center during weight bearing phase, and a high controllability in maintaining stability.